Intraocular Pressure Changes after Intravitreal Bevacizumab Injection Alone or Combination of Bevacizumab and Triamcinolone Acetonide - سليمان يوسف; جلول قحطان; بركات نور (Latakia University Journal -Medical Sciences Series, 2020)
Purpose: To evaluate intraocular pressure changes after intravitreal injection of Bevacizumab alone or in combination with Triamcinolone Acetonide. Method: Our study included 63 eyes from the ophthalmology department at Tishreen University Hospital who had vascular retinal diseases. The patients were divided into two groups according to the indication of injection. The first group was injected with bevacizumab (B) at a concentration of 2.5mg/0.1ml and the second group was injected with the combination treatment of Triamcinolone Acetonide at a concentration of 2mg/0.05ml with bevacizumab (B+TA) at a concentration of 1.25mg/0.05ml.Intraocular pressure was monitored on the Goldman applanation tonometry and values ​​were recorded as follows: before injection, the second injection day, a week after injection, a month after injection and after three months. Results: The mean values ​​of the intraocular pressure mean increased from the second day of injection in the study groups (B) and (B + TA) and the mean of the IOP values ​​before injection (13.34-13.31 mmHg) respectively, and the IOP values ​​showed the maximum in both groups after a week of the injection (17.81-17.31 mmHg) then began to decrease after a month and three months later to (17.34-17.06mmHg) and (17.6-16.75mmHg) mercury respectively, but they remained higher than they were before the injection, the number of injections had no effect on intraocular pressure. Conclusion: intravitreal injections with both bevacizumab alone or in combination with triamcinolone acetonide resulted in a rise in intraocular pressure, and differences in pressure values ​​were statistically significant within the same group during the studied time periods but were not statistically significant between the two groups, and the number of injections had no effect on intraocular pressure.